Faktor yang memengaruhi keputusan Cash Holding pada Perusahaan Manufaktur di Indonesia - Viriany, Jenny, (Jurnal Ekonomi, 2021)
This study aims to examine the relationship between Leverage, Cash Flow, and Net Working Capital on Cash Holding moderated by GCG. The dependent variable of this study is Cash Holding, the independent variable is Leverage, Cash Flow, and Net Working Capital, and the moderating variable is GCG. Manufacturing companies listed on the IDX during the 2017 to 2019 period were used as samples for this study using a purposive sampling research method. The total sample obtained by this method is 130 samples with a total of 390 observations. This study uses the panel data analysis method with a fixed-effect model as an estimation model. The results indicate that Leverage has a significant effect, meanwhile, Cash Flow and Net Working Capital have no significant effect on Cash Holding, and GCG proxied by the activities of the board of commissioners found cannot moderate the effect of all independent variables on Cash Holding significantly.